HUBUNGAN BEBAN KERJA CODER DENGAN KEAKURATAN KODE DIAGNOSA PASIEN RAWAT INAP DI RUMAH SAKIT SYAFIRA PEKANBARU - haryanio octaria; Warijan .; Anton Kristijono; Sugiharto . (Asosiasi Perguruan Tinggi Rekam Medis dan Informasi Kesehatan Indonesia- APTIRMIKI, 2017)
This code is flexible and accurate if it suitable with patient condition. In syafira hospital still found unaccuracy diagnosis code of patient hospitalization. This thing can be seen from the first time of survey (73,63) minutes that needed for 10 diagnoses only in 1 officer of coding. The purpose of this research was to know the relationship of coder workload and diagnosis code of accuracy patient hospital in pekanbaru 2016.The kind of this research is quantitative descriptive research. The sample was 114 persons which is random by using univariat and bivariat analysis with Chi Square.There is different of result in this research. Where can be seen from the accurate diagnosis; 84(73,7%), while there was bad accuracy 30(26,3%). The high workload 26 (22,8%) and the low workload; 88(72,2%). There was relationship the workload and code accurate P Value 0,00<0,05.